2018
DOI: 10.1016/j.apenergy.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of urban climate by extending the boundaries of urban energy system modeling

Abstract: Rapid growth of cities, concerns on global warming and depletion of fossil fuel resources call for sustainable energy solutions for cities. Distributed energy systems such as energy hubs offer promising solutions in this context. Evaluating the energy demand at urban scale is vital to support the design of energy hubs. However, most of the recent studies are based on bottom-up models and do not consider the energy demand in detail. More specifically, the influence of the urban climate on urban energy demand ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 56 publications
0
36
0
1
Order By: Relevance
“…Perera et-al. [117] extended the boundaries of the urban energy system model to incorporate the influence of urban climate. They showed that the urban climate is having a considerable impact on both the design and operation of the energy system.…”
Section: Section 43: Energy Demand and Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…Perera et-al. [117] extended the boundaries of the urban energy system model to incorporate the influence of urban climate. They showed that the urban climate is having a considerable impact on both the design and operation of the energy system.…”
Section: Section 43: Energy Demand and Supplymentioning
confidence: 99%
“…As explained in Section 3, both models were developed as an urban modelling platform that includes integrated custom modules for modelling microclimatic effects, transient heat flow, plants and equipment as well as occupant presence and behaviour. CitySim has furthermore been extended with the coupling with CIM and the energy hub tool to design urban energy systems [117]. Table 5 underlines the tools that are already available and their capabilities.…”
Section: Figure 4: Conceptual Integrated Workflowmentioning
confidence: 99%
“…Studies on Urban-Scale Energy Modeling (USEM) have shown the importance of morphological characteristics for the energy consumption of buildings [7]. The influence of urban form is considered important to optimize an energy system, together with the impact of the microclimate in built-up areas [8] and the characteristics of the outdoor environment [9]. These models also investigate the interaction between individual buildings and the urban context.…”
Section: Research Gapmentioning
confidence: 99%
“…Considering the limitation and negative impact of fossil fuels, renewable energy has become the focus of the global energy industry. Distributed energy systems (DES) offer promising solutions in this context, and their impact on urban power grids has drawn the attention of scholars [1,2]. Distributed generation (DG) has developed rapidly owing to its advantages, such as low pollution, high efficiency, and cost savings in power transmission and transformation infrastructure [3].…”
Section: Introductionmentioning
confidence: 99%